Cerebellum & Ataxias - Manto, Mario
Cerebellum & Ataxias is the first and only open access journal devoted to cerebellar research and cerebellar disorders, covering both research and clinical studies relevant to daily practice, including scientific reports and clinical cases of the numerous forms of ataxias. As the sister journal to The Cerebellum, we also publish clinical series, case reports, commentaries and teaching neuroimages. Highly recommended by contributing authors, the journal is of primary interest to neuroscientists, neuropsychologists, radiologists and clinicians dealing with neurological disorders in children and adults.